The Role Of Digital Marketing For Micro, Small And Medium Enterprises In The Era Of The Asean Economic Community - Alifah, Nur; Rohmat Hidayat, Agus; Elan Maulani, Isma (Journal of Comprehensive Science, 2023)
Today's technology continues to grow and users begin to feel the benefits of using the internet. Some feel dependence on the presence of the Internet, including the activities of Micro, Small and Medium Enterprises (MSMEs) using information technology in their business, especially in the era of the ASEAN Economic Community (AEC). The purpose of this study is to describe in general the impact of digital marketing on SME sales in Batam City. This research is qualitative in nature and uses a triangular model that combines structured interview methods, in-depth interviews and observations of MSMEs participants who actively participate in Market Community Improvement Services – Cooperatives and SMEs in the City. From the results of the study it can be seen that digital marketing facilitates communication and direct interaction between MSME players and consumers, increasing market share, increasing the visibility of MSME players and increasing sales.